PENINGKATAN PRODUKSI LAPANGAN “M” DENGAN PENDEKATAN SIMULASI UNTUK MENENTUKAN SKENARIO PENGEMBANGAN MENGGUNAKAN METODE WATERFLOODING - Maria Irmina Widyastuti; Maman Djumantara (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2016)
Reservoir simulation is an area of reservoir engineering in which computer models are used to predict the flow of fluids through porous media. Reservoir simulation process starts with several steps; data preparation, model and grid construction, initialization, history matching and prediction. Initialization process is done for matching OOIP or total initial hydrocarbon which fill reservoir with hydrocarbon control volume with volumetric method.To aim the best encouraging optimum data, the plant of developments of this field was predicted for 22 years( until December 2035). The Scenario consisted of five different variation. First one is basecase, second scenario is scenario 1 + workover, third scenario would be scenario 1 + infill wells, fourth scenario is scenario 1 + peripheral injection, and the last fifth scenario is scenario 1 + 5-spot injection pattern wells. From all of the scenarios planned, recovery from from each scenario varied, the results are 31.05% for the first scenario, 31.53%, for the second one, 34.12%, for the third, 33.75% for the fourth scenario, and 37.04% for the fifth scenario which is the last one.Keywords: reservoir simulation,reservoir simulator, history matching